GEOGRAPHICAL PERSPECTIVES ON HUMAN-ENVIRONMENT RELATIONSHIPS AND ANTHROPIC PRESSURE INDICATORS - DAN BĂLTEANU; DIANA DOGARU (Revue Roumaine de Géographie)
There is a growing literature on the study of human-environment relationships undertaken at various geographical scales. Tightly connected to the environmental change research, the topic of human-environment relationships deals primarily with the linkages between the social and physical systems, focusing on the human pressures onthe biogeochemical processes and the environmental effects on society. This paper outlines the main areas of interest in the human-environment relationship field, emphasizing the integrative character of this research subject. The authors then consider some methodological approaches to the assessment of human imprint on the environment and on the impacts of environmental change on society. Ultimately, the information extracted from theoretical and empirical studies on human-environment relationships was used as a background for a general framework of anthropic pressure indicators. There were identified three reference categories of anthropic pressure indicators, namely population; economic growth and resource consumption; urbanization. A brief discussion about the future research directions in the field of human-environment relationship research completes this paper.